2010
DOI: 10.1186/1475-2875-9-181
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring for Plasmodium falciparum drug resistance to artemisinin and artesunate in Binh Phuoc Province, Vietnam: 1998-2009

Abstract: BackgroundArtemisinin derivatives have been used for malaria treatment in Vietnam since 1989. Reported malaria cases have decreased from 1,672,000 with 4,650 deaths in 1991, to 91,635 with 43 deaths in 2006. Current national guidelines recommend artemisinin-based combination therapy (ACT), although artesunate is still available as monotherapy through the private sector. Recent reports suggest that effectiveness of ACT and artesunate monotherapy has declined in western Cambodia. This study examined Plasmodium f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 10 publications
(13 reference statements)
2
23
0
Order By: Relevance
“…However, for P. vivax, the assay options remain limited, and in view of the marked stage specificity of drug action, microscopic quantification of parasite growth remains the preferred option (12a, 17, 31). Previous studies have demonstrated that IC 50 estimates de- rived from schizont maturation tend to be higher than those derived by in vitro reinvasion assays with growth quantified by 3 Hhypoxanthine incorporation (1,23,36,39).…”
Section: Discussionmentioning
confidence: 95%
“…However, for P. vivax, the assay options remain limited, and in view of the marked stage specificity of drug action, microscopic quantification of parasite growth remains the preferred option (12a, 17, 31). Previous studies have demonstrated that IC 50 estimates de- rived from schizont maturation tend to be higher than those derived by in vitro reinvasion assays with growth quantified by 3 Hhypoxanthine incorporation (1,23,36,39).…”
Section: Discussionmentioning
confidence: 95%
“…Thanh and others 24 recently reported stable levels of P. falciparum sensitivity to artemisinins between 1998 and 2008-2009 in Vietnam, with a mean parasite clearance time ranging from 1.8 to 2.3 days. We used three different measures of parasite clearance: time to clearance of 100%, time to clearance of 95%, and slope half-life.…”
Section: Discussionmentioning
confidence: 97%
“…Monitoring data on drug resistance collected from 1998 to 2009 in the southern province of Binh Phuoc in Vietnam, bordering Cambodia, showed stable sensitivity of P. falciparum to artemisinins, both in vivo and in vitro (12). However, in 2010 and 2011 in the same area, the parasite clearance time was slower than in previous years (13).…”
mentioning
confidence: 94%